ANALISIS KUALITAS PELAYANAN KESEHATAN DI UPTD PUSKESMAS LEREP KABUPATEN SEMARANG - Siska Ariyani; Susi Sulandari (Journal of Public Policy and Management Review, 2019)
Lerep Public Health Center Semarang Regency is an institution that provides health services based on the regulations contained in the Health Ministry Regulation Numb. 75 Year 2014 concerning Public Health Center. The researcher is interested in examining the service quality at the UPTD Lerep Public Health Center because the researcher found several problems that are faced by the institution. Example coverage of health promotion and environmental health services, the cases of BTA+ that have met the target, the low claim for labor inpatient care, the low income for underpaid workers, the lack of employees, less parking area, and the very long handling time. The purpose of this study is to analyze service quality, employee capacity, and communication at the UPTD Lerep Public Health Center, and to analyze the correlation between the quality of health services and the ability of employees and the correlation between the quality of health services and communication. The research method used is quantitative with the population of patients.The sample was derived from 42 respondents from the population. The measurement used to find out how high the level of service quality at the UPTD Lerep Public Health Center, employees ability, and communication. The data analysis uses frequency distribution, the correlation used is a correlation using SPSS. The conclusion of this study shows that the level of quality of health services at the UPTD Lerep Public Health Center Semarang Regency is good. The correlation between the ability of employees and the strong service quality stands at 0.645 and the correlation between the communication and the strong service quality stands at 0.556. However, the result also shows that the institution still needs improvement in improving the quality of services, such as improvement in the service procedure, employee responsiveness and the role of the UPTD Lerep Public Health Center as a communicator.